The Influence of Profitability, Debt Policy and Investment Opportunities on Dividend Policy - Nisa, Khoirotun; Sinarasri, Andwiani (Economics and Business International Conference Proceeding, 2024)
This study aims to determine precisely the influence of profitability, debt policy and opportunity on dividend policy. The type of research used in this study is quantitative which has a population of all property sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The data collection technique in this study is purposive sampling. In this study, a sample of 23 property sector companies listed on the Indonesia Stock Exchange in 2018-2022 was studied. The technique used in analyzing the research data is Multiple Linear Regression with Micosoft Excel Application and SPSS Version 26 for research data processing. Based on the results of the hypothesis testing that has been conducted, it shows that Profitability has a positive effect on dividend policy and investment opportunities have a negative effect while debt policy has no effect on dividend policy.